Allicin ameliorates imiquimod‐induced psoriasis‐like skin inflammation via disturbing the interaction of keratinocytes with IL‐17A. (30th November 2022) - Zhang, Lu; Ma, Xuehong; Shi, Rongmei; Zhang, Libo; Zhao, Ruolin; Duan, Ran; Qin, Yuanyuan; Gao, Sijia; Li, Xinxia; Duan, Jingjing; Li, Jianguang
Abstract : Background and Purpose: Psoriasis is an inflammatory skin disease of chronic recurrence mediated by the interaction between IL‐17 and keratinocytes, which sustains a vicious circle of inflammation. Safe and effective natural medicine is a potential strategy for the clinical treatment of psoriasis. Given its prominent anti‐proliferative and anti‐inflammatory properties, we investigated the actions of allicin in improving psoriasis. Experimental Approach: Pharmacodynamic studies were carried out in mice after topical administration of allicin against psoriasis‐like lesions induced by imiquimod. Skin sensitization tests were evaluated on guinea pigs. Toxicological studies and skin irritation tests were assessed by consecutive topical allicin alone on the skin of rabbits. RNA‐seq probed transcriptomic changes following allicin. Western blot explored the actions of allicin on the interaction between IL‐17A and keratinocytes. Changes in inflammatory factor expression were analysed by qPCR and immunohistochemistry. Key Results: Allicin significantly improved the epidermal structure by inhibiting the excessive proliferation and reduced apoptosis of keratinocytes. Furthermore, allicin reduced the secretion of inflammatory cytokines (IL‐17A/F, IL‐22, IL‐12, and IL‐20), chemokines (CXCL2, CXCL5, and CCL20), and anti‐bacterial peptides (S100a8/9). Mechanistically, allicin directly inhibited the IL‐17‐induced TRAF6/MAPK/NF‐κB and STAT3/NF‐κB signalling cascades in keratinocytes, thus breaking the positive inflammatory feedback and alleviating imiquimod‐induced psoriasis‐like dermatitis in mice. Importantly, topical administration of allicin did not cause skin allergy, and the safety and adaptability of long‐term application were verified. Conclusions and Implications: Interfering with IL‐17 signalling in keratinocytes with allicin is a promising strategy for treating psoriasis, given its safety and effectiveness.